Pengaruh Kemiringan Jalan dan Jarak Terhadap Pengisian Kapasitor Bank Pada Sepeda Hybrid - Bhintoro Satria Wibawa Putra Artino; Azam Muzakhim Imammuddin (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Capacitor bank is an arrangement of capacitors in series or parallel that can store energy temporarily and provide limited energy according to its capacity. Basically, a capacitor is composed of two parallel pieces called electrodes separated by a room called a dielectric which when given a voltage will store energy. The purpose of this study is to determine the effect of road slope and distance on charging in capacitor banks. In this study used a 2.7 V 500F capacitor and used a generator that has a specification of 300 watts. In this study using a quantitative experimental method that aims to determine the effect of road slope variations of 20⁰ and 25 ⁰ and with distances of 100m, 300m, 500m, 700m, and 900m. Testing is done by measuring the voltage on the capacitor bank using a multitester and indicator by utilizing a data logger and the percentage of voltage capacity on the capacitor bank. Furthermore, the data will be processed in the table using minitab. In the research results, it was concluded that the longer the distance traveled, the more the charging voltage value on the capacitor bank increased. For the effect of road slope on the voltage value on charging capacitor banks does not have a significant effect and for the effect of the interaction between road slope and distance has no effect on the voltage value.